Biografía. R.M. Schindler. (1998)
Reseña de los antecedentes académicos y profesionales del arquitecto vienés.
Keywords: BIOGRAFIAS; SCHINDLER, R. M; HISTORIA; ARQUITECTURA; AUSTRIA; ESTADOS UNIDOS; MOVIMIENTO MODERNO